Efektivitas Green Marketing, Kualitas Produk dan Kualitas Kemasan Berbasis Ekonomi Hijau terhadap Sustainability Bisnis UMKM Ritel - Hasanudin, Hasanudin; Baharsyah, Syamsudin; Satrio, Bayu (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study was to analyze the influence of green marketing, product quality, and green economy-based packaging quality on the sustainability of retail MSMEs in Bogor Regency. This study adopted a quantitative method with an associative approach. Respondents in this study were 50 retail MSME entrepreneurs with predetermined criteria. The results showed that simultaneously there was a significant influence between the variables of green marketing, product quality, and packaging quality, which had a positive and significant effect on the sustainability variable of MSME businesses. However, partially only the green marketing variable did not affect the sustainability of retail MSME businesses in Cikeas Udik, Bogor Regency.